Biodrainage for Restoration of Canal Command Waterlogged Area in Indian Desert - Bala, N.; Singh, G.; Bohra, N. K.; Limba, N. K.; Baloch, S. R. (Indian Forester, 2014)
An attempt was made to remove excess water from the land through bio-drainage and to increase vegetation cover and productivity of a waterlogged area in Indian desert. Area protection, soil working and plantation of Eucalyptus camaldulensis, E. fastigata, E. rudis and Corymbia tessellaris on raised bunds, improved vegetation cover with simultaneous decrease in water table. Performance of E. rudis was best with respect to growth, biomass, transpiration rate and overall bio-drainage potential. E. rudis maintained uniform transpiration and photosynthesis rate throughout the year. Ground water level receded by 145 cm in E. rudis plot compared to 90 cm, 70 cm and 60 cm in C. tessellaris, E. camaldulensis and E. fastigata respectively within a period of four and half year. Soil organic carbon, electrical conductivity, NH and NO - N were high in E. rudis and low in E. fastigata. The results suggests that E. rudis has high 4 3 potential to be used as an efficient bio-drainage species in canal command waterlogged area of Indian desert. Apart from the planted species, Prosopis juliflora, Tamarix dioca and Saccharum munja also have come up in the area with recession of ground water table as natural succession and contributed significantly for further lowering of ground water table and increasing productivity.